2018
DOI: 10.1016/j.prp.2017.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Wnt/β-catenin signal alteration and its diagnostic utility in basal cell adenoma and histologically similar tumors of the salivary gland

Abstract: Differential diagnosis among basal cell adenoma (BCA), basal cell adenocarcinoma (BCAC), adenoid cystic carcinoma (ACC) and pleomorphic adenoma (PA) of the salivary gland can be challenging due to their similar histological appearance. Although frequent nuclear β-catenin expression and CTNNB1 mutations have been reported in BCA, further details of the Wnt/β-catenin signal alterations are unclear. The aim of this study was to assess the diagnostic utility of Wnt/β-catenin signal alteration in BCA and morphologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 34 publications
(59 reference statements)
0
26
0
Order By: Relevance
“…In addition to fusion genes resulting from chromosomal rearrangements, certain hotspot mutations of oncogenes are closely linked to particular histological entities, e.g. CTNNB1 mutations in basal cell adenoma/adenocarcinoma, PRKD1 mutations in polymorphous adenocarcinoma, and HRAS mutations in epithelial–myoepithelial carcinoma . The characterisation of the histological and genetic features of minor salivary papillary–cystic tumours leads to an understanding of tumorigenesis and refinement of the tumour classification.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to fusion genes resulting from chromosomal rearrangements, certain hotspot mutations of oncogenes are closely linked to particular histological entities, e.g. CTNNB1 mutations in basal cell adenoma/adenocarcinoma, PRKD1 mutations in polymorphous adenocarcinoma, and HRAS mutations in epithelial–myoepithelial carcinoma . The characterisation of the histological and genetic features of minor salivary papillary–cystic tumours leads to an understanding of tumorigenesis and refinement of the tumour classification.…”
Section: Introductionmentioning
confidence: 99%
“…Its nuclear expression was typical and specific for BCA. Sato et al demonstrated that Wnt/β-catenin signal alteration plays a role in the pathogenesis of BCA ( 4 ). Our data showed that all the selected AdCCs in our study had membrane immuno-activity of β-catenin.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggested that β-catenin mutation was present in up to 52% of BCAs. Thus, the corresponding nuclear expression of β-catenin can be detected in BCA and would be a specific marker to identify cBCA or iBCA from AdCC (4). At the same time, few BCAs have incomplete capsules or could have focal capsule invasion, which are easily mistaken as malignant presentation.…”
Section: Introductionmentioning
confidence: 99%
“…The inner ductal cells typically stain for CK7 but the outer myoepithelial cells are positive for more typical myoepithelial marker such as SMA. p63 and high-molecular weight cytokeratins [81,82] (Fig. 2e, f).…”
Section: Basal Cell Adenomamentioning
confidence: 94%